2019
DOI: 10.1175/mwr-d-18-0292.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative View on the Processes Governing the Upscale Error Growth up to the Planetary Scale Using a Stochastic Convection Scheme

Abstract: Two diagnostics based on potential vorticity and the envelope of Rossby waves are used to investigate upscale error growth from a dynamical perspective. The diagnostics are applied to several cases of global, real-case ensemble simulations, in which the only difference between the ensemble members lies in the random seed of the stochastic convection scheme. Based on a tendency equation for the enstrophy error, the relative importance of individual processes to enstrophy-error growth near the tropopause is quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 36 publications
9
62
0
Order By: Relevance
“…To attribute the evolution of forecast uncertainty to individual processes, we extend our recently developed PV diagnostic for error growth (Baumgart et al . ) to the evolution of ensemble variance. In isentropic coordinates and the primitive‐equations framework, Ertel () PV is defined as follows: P=gθp()ζθ+f0.1em, where g is the gravitational acceleration, θ the potential temperature, p the pressure, ζ θ the vertical component of the isentropic relative vorticity, and f the Coriolis parameter.…”
Section: Data and Methods To Quantify The Amplification Of Forecast Umentioning
confidence: 88%
See 2 more Smart Citations
“…To attribute the evolution of forecast uncertainty to individual processes, we extend our recently developed PV diagnostic for error growth (Baumgart et al . ) to the evolution of ensemble variance. In isentropic coordinates and the primitive‐equations framework, Ertel () PV is defined as follows: P=gθp()ζθ+f0.1em, where g is the gravitational acceleration, θ the potential temperature, p the pressure, ζ θ the vertical component of the isentropic relative vorticity, and f the Coriolis parameter.…”
Section: Data and Methods To Quantify The Amplification Of Forecast Umentioning
confidence: 88%
“…Interestingly, the variance tendency in ridge R3 (around 10–40°W), which was dominated by the divergent tendency at 2 days (Figure ), is now dominated by the near‐tropopause tendency, indicating a multi‐stage behaviour of variance amplification, as was observed for upscale error growth (Baumgart et al . ).…”
Section: Quantitative View Of the Variance Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…After five days, the PV250 differences due to the MCS perturbations lay along the tropopause, consistent with findings from previous studies of error growth related to the representation of moist processes using PV‐based analysis (Schäfler and Harnisch, ; Joos and Forbes, ; Baumgart et al . ), but the position of these differences varied between the ensemble members, corresponding to the different Rossby‐wave structures generated by the IC perturbations. Despite this variability, the MCS perturbations have been shown systematically to shift the location of a surface low‐pressure system over northern Russia, downstream of the location where the MCS perturbations were inserted, to the west of northwest; this shift is consistent with other studies that have found slowed eastwards Rossby‐wave propagation due to intense convection (Riemer et al .…”
Section: Discussionmentioning
confidence: 98%
“…The impact of differences in the representation of convection on upscale error growth has been investigated by Baumgart et al . () by applying diagnostics based on PV and the envelope of Rossby waves to convection‐parametrizing ensemble forecasts that use the Plant–Craig stochastic convection scheme (Plant and Craig, ). Similar to the findings in our study, they found that the strong PV gradient associated with the tropopause is displaced by error growth associated with moist processes occurring below (with associated latent heat release) and upper‐level divergence projects these errors effectively into the tropopause region.…”
Section: Downstream Influence Of Mcs Perturbations: Overviewmentioning
confidence: 99%